2020
DOI: 10.1103/physrevd.101.044060
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic stars in mass-varying massive gravity

Abstract: Mass-varying massive gravity allows the graviton mass to vary according to different environments. We investigate neutron star and white dwarf solutions in this theory and find that the graviton mass can become very large near the compact stars and settle down quickly to small cosmological values away the stars, similar to that of black holes in the theory. It is found that there exists a tower of compact star solutions where the graviton mass decreases radially to zero non-trivially. We compute the massive gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Yet another generalization of massive gravity is the so-called mass-varying massive gravity, where the mass of the graviton varies depending on the value of the scalar field [305]. Neutron stars in this model were studied by Sun and Zhou [160] using analytic fits of APR and SLy EOS. It is found that, depending on the value of the mass, m, appearing on a simple quartic potential, the maximum mass in both EOS can significantly increase by a factor ∼ 10% − 20% (with negligible modifications in the corresponding radius), though whether the parameters chosen are observationally viable is not discussed.…”
Section: Massive Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another generalization of massive gravity is the so-called mass-varying massive gravity, where the mass of the graviton varies depending on the value of the scalar field [305]. Neutron stars in this model were studied by Sun and Zhou [160] using analytic fits of APR and SLy EOS. It is found that, depending on the value of the mass, m, appearing on a simple quartic potential, the maximum mass in both EOS can significantly increase by a factor ∼ 10% − 20% (with negligible modifications in the corresponding radius), though whether the parameters chosen are observationally viable is not discussed.…”
Section: Massive Gravitymentioning
confidence: 99%
“…Super-Chandrasekhar white dwarfs have been also investigated within some extensions of massive gravity[160] and in non-commutative geometries[161], finding a theoretical maximum limit of 2.9M ⊙ in the former, and 2.6M ⊙ in the latter.…”
mentioning
confidence: 99%
“…As one can see, the highly expected breaking of spherical symmetry and the absence of strong magnetic fields in isolated white dwarfs, leads to an open window for other mechanisms that could also violate the Chandrasekhar limit. One such mechanism would be modified gravity [29][30][31][32][33][34][35][36][37][38][39][40]68]. In Ref.…”
Section: Massive White Dwarfs On the Grounds Of Modified Gravitymentioning
confidence: 99%
“…In this context, plenty of works have been done to model these very massive white dwarfs (MWD). The properties of MWDs have been studied in different contexts: rotation [7][8][9][10]; high electric and magnetic fields [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; temperature [27,28] and modified gravity [29][30][31][32][33][34][35][36][37][38][39][40]. It has been shown that general relativistic effects are essential for massive white dwarfs and cannot a e-mail: r.vieira@uniandes.edu.co b e-mail: araujogc@ita.br c e-mail: nkelkar@uniandes.edu.co d e-mail: mnowakos@uniandes.edu.co (corresponding author) be disregarded [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, plenty of works have been done to model these very massive white dwarfs (MWD). The properties of MWDs have been studied in different contexts: rotation [7-10]; high electric and magnetic fields [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; temperature [27,28] and modified gravity [29][30][31][32][33][34][35][36][37][38][39][40]. It has been shown that general relativistic effects are essential for massive white dwarfs…”
mentioning
confidence: 99%